2014
DOI: 10.1016/j.rmed.2014.05.013
|View full text |Cite|
|
Sign up to set email alerts
|

Extrafine beclomethasone/formoterol in severe COPD patients with history of exacerbations

Abstract: The FORWARD study is a randomised, double-blind trial that compares the efficacy and safety of 48 weeks treatment with extrafine beclomethasone dipropionate/formoterol fumarate (BDP/FOR), 100/6 μg pMDI, 2 inhalations BID, vs. FOR 12 μg pMDI, 1 inhalation BID, in severe COPD patients with a history of exacerbations. Co-primary endpoints were exacerbation rate over 48 weeks and pre-dose morning FEV(1) at 12 weeks. The ITT population included 1186 patients (69% males, mean age 64 years) with severe airflow limita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
1
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 29 publications
6
81
1
4
Order By: Relevance
“…The results of the study have been reported (6) and showed a significant reduction in exacerbation rate (28%) and improvement in lung function with BDP/FF compared with FF treatment.…”
Section: To the Editormentioning
confidence: 77%
“…The results of the study have been reported (6) and showed a significant reduction in exacerbation rate (28%) and improvement in lung function with BDP/FF compared with FF treatment.…”
Section: To the Editormentioning
confidence: 77%
“…In particular, in the two replicate 1-year studies, a pooled analysis demonstrated fewer moderate and severe exacerbations in all fluticasone/vilanterol groups (0.93e0.81 exac/pt/yr) in comparison with vilanterol alone (1.11 exac/pt/yr) [26]. The other new combination, beclometasone/formoterol combination in the extrafine formulation, has been demonstrated more effective that formoterol alone in reducing the rate of moderate and severe exacerbations (OR: 0.72, CI: 0.62e0.84) [27]. Because data on these new combinations are limited, they were not included in the overall evaluation of efficacy and safety of ICS/LABA combinations in COPD.…”
Section: Comparative Clinical Efficacy Of Fluticasone/salmeterol and mentioning
confidence: 94%
“…В исследовании FORWARD при терапии экстрамелкодисперсной комбинацией бекломета зона дипропионат / формотерол в течение 48 нед. риск обострений ХОБЛ снизился на 28 % по сравне нию с формотеролом (ОР -0,72; 95% ный ДИ -0,62-0,84) [111]. По результатам объединенного ана лиза 2 рандомизированных исследований также по казано, что при лечении комбинацией флутиказона фуроат / вилантерол по сравнению с монотерапией вилантеролом достоверно снижается риск среднетя желых и тяжелых обострений ХОБЛ [112].…”
Section: игкс и комбинации игкс / ддбаunclassified